O redukci a vylučování ve studiu mystiky = On reduction and exclusion in the study of mysticism - Vaněk, David (Religio, 1998)
The article deals with the recent criticism of the so-called classical study of mysticism, undertaken by Katz, Hollenback and Penner. It attempts to show that the central point of the discussion is the problem of the ineducibility of mystical phenomena. Although Otto, Underhill, Stace and others have been criticized for excluding the mystical from the rest of the reality, attributing to it some unique ontological and epistemological nature, their critics proved themselves unable to venture the real reduction. Their relation to it remains ambivalent: on the one hand, they are critical of the classics' quest for a totally exclusive experience, on the other hand, they employ various strategies to preserve exclusivity on the level of the particular cultural and historical context, defending the mystics against "essentialistic reductionism" and ethnocentrism. Such an attempt entails, however, another ethnocentric (or scientistic) statement: epistemological and ontological reflection has to be of no value for the mystics' view of their own experience. Mysticism may be unique because it has no concem with philosophy. Instead of such an ambivalence in relation to the philosophical reduction, the author of the article proposes to take both philosophy and the mystics' account of their experience seriously and confront each other as strongly as possible, disregarding possible accusations of the scientistic and cultural violence.